Proverbs in Language Teaching: Using the Example of Let’s Speak Tigrinya (2018) - Busau, Filip (Aethiopica, 2020)
Proverbs have been used in language teaching for centuries. Nowadays, language learners associate mastery of this traditionally oral genre to a certain level of fluency and regard it as an access key to a deeper understanding of the native speakers’ culture. The recently released Tǝgrǝñña coursebook Let’s Speak Tigrinya (2018) contains almost fifty proverbs, and provides students with an insight into this old and rich tradition. However, owing to the lack of commentary or translation, the paper here seeks to compensate for this deficiency. In comparison with several Tǝgrǝñña proverb collections, it becomes apparent that the expressions listed in the textbook are common in Eritrea as well as in the Tǝgray region, in several alternative variations, some of which have been attested to in earlier European research works. A few examples even have an Amharic equivalent. The proverbs focused on here cover a wide range of both grammatical and everyday life topics and should be implemented in a more effective manner than the textbook provides. However, due to the lack of translations and occasional misprints, their accessibility is radically reduced and of little use for the individual language learner unassisted by a classroom situation.